Relationships Between Registered Nurse Staffing, Processes of Nursing Care, and Nurse-Reported Patient Outcomes in Chronic Hemodialysis Units - Thomas-Hawkins, Charlotte (2008)
Little attention has been given to the effects of registered nurse (RN) staffing and processes of nursing care on patient outcomes in hemodialysis units. This research examined the effects of patient-to-RN ratios and necessary tasks left undone by RNs on the likelihood of nurse-reported frequent occurrences of adverse patient events in chronic hemodialysis units. Study findings revealed that high patient-to-RN ratios and increased numbers of tasks left undone by RNs were associated with an increased likelihood of frequent occurrences of dialysis hypotension, skipped dialysis treatments, shortened dialysis treatments, and patient complaints in hemodialysis units. These findings indicate that federal, state, and dialysis organization policies must foster staffing structures and processes of care in dialysis units that effectively utilize the invaluable skills and services of professional, registered nurses.